Corrosion resistance and surface microstructure of Mg3N2/SS thin films by plasma focus instrument - Habibi, Maryam; Sadeghi, Mohammad; Arman, Ali; Sobola, Dinara; Luna, Carlos; Mirzaei, Saeed; Zelati, Amir; Fonseca Filho, Henrique Duarte; Ţălu, Ştefan (Microscopy research and technique, 2022)
Utilizing a plasma focus (PF) instrument, magnesium nitride (Mg3N2) thin films were synthesized on stainless steel substrates. Twenty five optimum focus shots at 8 cm distance from the anode tip were used to deposit the films at different angular positions regarded to the anode axis. Scanning electron microscopy (SEM), atomic force microscopy (AFM), and X‐ray diffraction (XRD) analyses were performed to assess the surface morphology and structural characteristics of Mg3N2 films. Based on AFM images, these films were studied to understand the effect of angular position variation on their surfaces through morphological and fractal parameters. By increasing the angle, we verify that the grain size decreased from 130(0) nm to 75(5) nm and also the mean quadratic surface roughness of the films reduced in its average values from (28.97 ± 3.24) nm to (23.10 ± 1.34) nm. Power spectrum density analysis indicated that films become more self‐affine at larger angles. Furthermore, the corrosion behavior of the films was investigated through a potentiodynamic polarization test in H2SO4 solution. It was found that the ion energy and flux, varying with the angular positions from the anode tip, directly affected the nanostructured roughness and surface morphology of the samples. The electrochemical studies of films show that the uncoated sample presented the lowest corrosion resistance. The highest corrosion resistance was obtained for the sample deposited with 25 optimum shots and at 0° angular position reaching a reduction in the corrosion current density of almost 800 times compared to the pure stainless steel‐304 substrate. Highlights Mg3N2/SS films have been deposited at different angles by plasma focus (PF) instruments. The effect of angular position on the surface microtexture, morphological parameters, and corrosion features of the films was studied. The RBS measurement and X‐ray diffraction are utilized to identify the crystalline phases and thickness of films. Relevant parameters of the watershed segmentation definition and potentiodynamic polarization curves.